2019
DOI: 10.1287/opre.2018.1800
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Pricing in Ride-Sharing Networks

Abstract: Motivated by the prevalence of ride-sharing platforms, in “Spatial Pricing in Ride-Sharing Networks,” Bimpikis, Candogan, and Saban explore the impact of the demand pattern for rides across a network’s locations on a platform’s optimal pricing and compensation policy, profits, and consumer surplus. They explicitly account for the pricing problem’s spatial dimension and the fact that the drivers endogenously determine whether and where to provide service. Their first contribution is to develop a tractable model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
99
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 381 publications
(113 citation statements)
references
References 14 publications
3
99
2
Order By: Relevance
“…Ridesharing has long been a research hotspot in the transport field, previous studies have discussed the ridematching algorithms for ridesharing systems [2][3], dynamic ridesharing pricing [4][5], labour supply [6], trust among peers [7][8], socio-economic impacts of ridesharing services [9], environmental effects of ridesharing [10][11] Some scholars began to pay close attention to the impact of ridesharing on traffic congestion. There are different voices on distinguishing an impact of ridesharing on traffic.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Ridesharing has long been a research hotspot in the transport field, previous studies have discussed the ridematching algorithms for ridesharing systems [2][3], dynamic ridesharing pricing [4][5], labour supply [6], trust among peers [7][8], socio-economic impacts of ridesharing services [9], environmental effects of ridesharing [10][11] Some scholars began to pay close attention to the impact of ridesharing on traffic congestion. There are different voices on distinguishing an impact of ridesharing on traffic.…”
Section: Literature Reviewmentioning
confidence: 99%
“…2). The demand q of the OD pair (1,4) was set to 400. The details on ta, l a , and c a are shown in Tab.…”
Section: Case Studymentioning
confidence: 99%
“…The sharing economy, which is characterized by the sharing of usage rights, creates a great prospect about the potential sustainability benefits [29]. Current research on sharing economy focuses on collaborative consumption in the field of transportation [18], space [19], and durable goods [20]. Wu et al [30] studied the sharing economy from an environmental perspective and found that the sharing economy could help to allocate resources and reduce greenhouse gas emissions.…”
Section: Literature On Production Capacity Sharingmentioning
confidence: 99%
“…In recent years, although the issues about the production capacity sharing have attracted some scholars, this topic is still in its infancy. Firstly, scholars are keen to study capacity sharing in the field of consumption such as transportation, space, and durable goods [18][19][20], where the system generally consists of three parties: suppliers, demanders and sharing platforms. However, there are four parties repeated), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Note that our survey reviews the papers that focus on operational decisions made by the P2P ride-sharing system operator, including the matching, routing, and scheduling of users. Therefore, this survey does not include the study of economics (Wang et al 2018a, Zha et al 2018b, Bimpikis et al 2019 and/or user equilibrium analyses (Wang et al 2018b) involved in such systems. Compared with the existing surveys (Agatz et al 2012, Chan and Shaheen 2012, Furuhata et al 2013, Ordóñez and Dessouky 2017, the contributions of this paper are threefold: (i) it includes the related work that has appeared since then, (ii) it delves into details of the proposed algorithms, and (iii) it identifies new directions for research.…”
Section: Introductionmentioning
confidence: 99%